Indirect Control of a Doubly-Fed Induction Machine for Wind Energy Conversion - Smail Mansouri; Ali Benatillah (Institute of Advanced Engineering and Science, 2014)
In this paper, a grid connected wind power generation scheme using a doubly fed induction generator ( DFIG) is studied. The aims of this paper are: The modelling and simulation of the operating in two quadrants (torque-speed ) of a DFIG, the analysis employs a stator flux vector control algorithm to control rotor current, the system enables optimal speed tracking for maximum energy capture from the wind and high performance active and reactive power regulation using the PI regulator. The simulation calculations were achieved using MATLAB®-SIMULINK® package. Lastly, the obtained results are presented, for different operating points, illustrating the good control performances of the system.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5944